Occupational Stress and its Relation to Grave’s Disease - Ade Mutiara; Dewi S Soemarko; Indah S Widyahening (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background: Graves’ disease is an autoimmune thyroid gland disease that causes increased activity of the thyroid hormones. But, the mechanism by which the autoantibodies are generated is still unclear. Some theory suggests that daily life stress may be a risk factor that triggers Graves’ disease. The aim of this report is to enrol a systematically searching in order to get an answer about the risk factor of the Grave’s disease and the prevention measure.Methods: In this case report, a 47-year-old career woman with prominent occupational stress was diagnosed with Graves’ disease. Literature searching was done on database such as Pubmed, Cochrane Library, and Science Direct with occupational stress, stressful life event, and Graves’ disease as the keywords. One article was selected and critically appraised. Results: One case-control study showed that patients with Graves’ disease had odds ratio (OR) of having stressful life events as big as 8.59; 95%CI = 2.35-20.80, and the number needed to harm (NNH) is 2.35.Conclusion: Occupational stress is a prominent risk factor for developing Graves’ disease. However, this is based on one article